(untitled) (Al Insyirah International Scientific Conference on Health, 2023)
Currently, the elderly are one of the comorbid groups that are vulnerable to COVID 19, in the situation of the Corona Virus pandemic, usually anxiety comes in various forms including fear of death, this happens because of seeing the death rate due to the corona outbreak which is getting bigger day by day. The purpose of the study identified a picture of elderly anxiety as a comorbid Covid 19 in the city of Sedinginan, Rokan Hilir.Riau Regency. The design of this study is descriptive with a cross sectional approach. The research was carried out for 1 month from June 2021 to July 2021. Meanwhile, the research site was conducted in Sedinginan Village, Rokan Hilir Riau Regency, in 2021. The population is elderly in Sedinginan City, Rokan Hilir Riau Regency as many as 60 people with the "total sampling" method and research instruments using questionnaires. Univariate analysis is displayed in the frequency distribution. Result: research shows that out of 60 elderlies, the most elderly with high anxiety are 37 people (61,7%). Conclusion: that the elderly is of a high category and are recommended for the elderly to be able to control and manage anxiety well and can increase knowledge about the dangers of COVID-19 to the elderly so that they understand how to prevent the elderly from contracting COVID-19